2004
DOI: 10.1002/asi.20041
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional approach to the study of human‐information interaction: A case study of collaborative information retrieval

Abstract: While most research in the area of human-information behavior has focused on a single dimension-either the psychological or the social-this case study demonstrated the importance of a multidimensional approach. The Cognitive Work Analysis framework guided this field study of one event of collaborative information retrieval (CIR) carried out by design engineers at Microsoft, including observations and interviews. Various dimensions explained the motives for this CIR event and the challenges the participants enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 35 publications
2
85
0
8
Order By: Relevance
“…As task complexity increases, the need for domain and problemsolving information increases and the number of sources increase. Fidel et al [14] studied on collaborative information retrieval. They defined task analysis in decision-making terms and in terms of strategies as characteristics of cognitive work.…”
Section: Task Environment For Knowledge Workersmentioning
confidence: 99%
“…As task complexity increases, the need for domain and problemsolving information increases and the number of sources increase. Fidel et al [14] studied on collaborative information retrieval. They defined task analysis in decision-making terms and in terms of strategies as characteristics of cognitive work.…”
Section: Task Environment For Knowledge Workersmentioning
confidence: 99%
“…Understanding how we interact with systems (including each other) is a key to designing better tools to help us carry out whatever work we're tasked to complete. Related research has focused on academics, students, people in the healthcare field and janitors (Chatman, 1991;Fidel, Mark Pejtersen, Cleal, & Bruce, 2004;Pettigrew, Fidel, & Bruce, 2001;Savolainen, 2009;Solomon, 1997;Diane H Sonnenwald & Iivonen, 1999;Thomas D Wilson, 2000). One group, however that has not been closely studied is law enforcement.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“….Meanwhile, a multidimensional approach was suggested to study the collaborative information interaction by Fidel, Mark Pejtersen, Cleal, and Bruce [20] to include the cognitive dimension of individuals along with the specific task and decision, the organization of the teamwork, and the organizational culture, the same study recommended more multidimensional studies to enhance understanding of collaborative information behaviour, with this approach the study suggested to consider the social and organizational environment when studying collaborative information practice and that collaborative work should include a system that supports interactions between actors to "enhance their access to one another's knowledge, ideas, and opinions or help them keep on track"…”
Section: Information Seeking Behaviour Of Engineers and Engineering Smentioning
confidence: 99%